1997
DOI: 10.1126/science.275.5305.1475
|View full text |Cite
|
Sign up to set email alerts
|

PTG, a Protein Phosphatase 1-Binding Protein with a Role in Glycogen Metabolism

Abstract: Protein dephosphorylation by phosphatase PP1 plays a central role in mediating the effects of insulin on glucose and lipid metabolism. A PP1C-targeting protein expressed in 3T3-L1 adipocytes (called PTG, for protein targeting to glycogen) was cloned and characterized. PTG was expressed predominantly in insulin-sensitive tissues. In addition to binding and localizing PP1C to glycogen, PTG formed complexes with phosphorylase kinase, phosphorylase a, and glycogen synthase, the primary enzymes involved in the horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
294
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(307 citation statements)
references
References 19 publications
10
294
1
Order By: Relevance
“…In addition to targeting PP1 to the glycogen particle, PTG can also form complexes with PP1 substrate enzymes that regulate glycogen metabolism, namely glycogen synthase, glycogen phosphorylase, and phosphorylase kinase. In this case, PTG not only binds PP1C and glycogen but also co-localises PP1 with its substrate at the glycogen particles suggesting that PTG is responsible for assembling metabolic enzymes for the localised reception of intracellular signals [23,24]. In a similar way, the present experiments suggest that GM, which targets PP1C to both glycogen particles and the SR of striated muscle [13], may localise PP1C close to its PLB substrate in order to control speci¢cally the activation of the calcium ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to targeting PP1 to the glycogen particle, PTG can also form complexes with PP1 substrate enzymes that regulate glycogen metabolism, namely glycogen synthase, glycogen phosphorylase, and phosphorylase kinase. In this case, PTG not only binds PP1C and glycogen but also co-localises PP1 with its substrate at the glycogen particles suggesting that PTG is responsible for assembling metabolic enzymes for the localised reception of intracellular signals [23,24]. In a similar way, the present experiments suggest that GM, which targets PP1C to both glycogen particles and the SR of striated muscle [13], may localise PP1C close to its PLB substrate in order to control speci¢cally the activation of the calcium ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…PTG, also called R5, binds glycogen and is implicated in the control of glycogen metabolism [24]. PTG has been proposed to act as a scaffold, binding also to glycogen synthase, phosphorylase and phosphorylase kinase [24].…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Another connection to glycogen came from the yeast two hybrid screen described by Fernandez-Sanchez et al [18] which identified the type 1 protein serine/threonine phosphatase regulatory subunit, PTG. PTG, also called R5, binds glycogen and is implicated in the control of glycogen metabolism [24]. PTG has been proposed to act as a scaffold, binding also to glycogen synthase, phosphorylase and phosphorylase kinase [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include genes that are variously required for control of glycogen metabolism, glucose repression, meiosis and/or sporulation, and mitotic cell cycle regulation (19 -21). Thus, PP1 is unusual in that this single enzyme is involved in the regulation of a number of diverse cellular processes.Few, if any, of the PP1 proteins share any major sequence identity, although examination of different glycogen-binding subunits has revealed the presence of two small regions of sequence similarity that is shared between several glycogenbinding proteins (20,(22)(23)(24)(25). The unusually large number of PP1-binding proteins that have been described suggests either that PP1 contains a motif that is recognized by a common binding structure on this diverse group of proteins or that the latter contain a protein motif that is recognized by a single binding site on PP1.…”
mentioning
confidence: 99%